Use of Mobile Phones in Mobile Assisted Language Learning (MALL) - Poudel, Ambika Prasad (ILAM इलम, 2025)
The advancement of Information and Communication Technologies (ICTs) and their exploitation have caused significant changes in language pedagogy. Mobile Assisted Language Learning (MALL), a new pedagogical approach, is becoming increasingly popular among ELT practitioners in recent years, and the use of mobile phones in MALL is an example of a noticeable development in ICT exploitation. This study aims to explore the role and place of mobile phones, particularly smartphones, in MALL activities in the context of higher education in Nepal. Adopting the phenomenological research design and conducting interviews with university students, this study found that mobile phones are ubiquitous and multi-functional devices which can be used as effective tools for language learning. The smartphones are useful for English language learners for improving their pronunciation, vocabulary, grammar, and language skills, specifically listening and reading. The study concluded that it is important to encourage the proper use of mobile phones inside and outside the classroom to facilitate English language learning.